Statlig politikk og lokale utfordringer Organisering av tjenester innen rus og psykisk helse - Bjørkquist, Catharina; Ramsdal, Helge (Cappelen Damm Akademisk/NOASP (Nordic Open Access Scholarly Publishing), 2021)
The services for people with addiction and mental health problems and have received increasing attention, both in the public debate, among users and professionals and not least from political authorities. There is political agreement on the importance of prioritizing the field, when at the same time there is disagreement on whether the services will actually be better by present-day reforms. In National Policies and Local Challenges, the authors explore the organization of services for people with addiction and mental health illness, from initiatives to improve the services at the level of national government to implementing changes in local service provision by municipalities. We discuss one of the most challenging questions in the modern welfare state: How should services be organized so that both users and service providers experience them as coordinated and integrated? The authors address these issues by referring to key features of national policy and change processes that can be observed in a selection of municipalities. The book also refers to analyses of experiences with various measures and services related to work, housing and prison care and correctional services. The anthology is based on a research project that studies the coordination and integration of services for people with complex addiction and mental disorders. The book is based on political science and organizational theoretical perspectives, and aims to provide insight into the usefulness of such perspectives in the analysis of welfare state's challenges when complex needs are addressed. The target group for the book is researchers, students and employees in local government - as well as practitioners who work with users with complex and complex needs. The book is edited by Catharina Bjørkquist, professor at Østfold University College, and Helge Ramsdal, professor emeritus at Østfold University College.